Step-By-Step Design and Calculations for Water Treatment Plant Units: A Recent Study - Aziz, Shuokr Qarani; Mustafa, Jwan Sabah (Modern Advances in Geography, Environment and Earth Sciences Vol. 4, 2021)
This work presented the design steps and calculation for each unit of the water treatment plant (WTP), due to its crucial role domestically and drinking purpose. It also illustrated and designed the procedures of the water processing units by estimating water demand and designing the unit process. The objectives of this work were to evaluate the water demand for a certain community and to present design steps and calculations for the required units of a WTP. The design of the WTP units was applied to Greater-Zab River water for the selected location in Erbil City-Iraq. The quality and quantity of the Greater-Zab River water at various times were statistically analyzed and presented. The units of the treatment processes involved intake, coagulation, flocculation, sedimentation, adsorption (optional), filtration, disinfection, storage, and pumping. The calculations and detailed drawings of the units were displayed, the average discharge and population used for the WTP design were 60,000 m3/day and 200,000, respectively. Besides, the calculation required some of the parameters to be estimated as field data, which were taken into consideration. The outline results of each unit of the WTP were tabulated. The quality and quantity of the surface water source affected the WTP design. It can be concluded that this work can be used as a source for designing other WTP units. A number of factors such as the age of WTP, maintenance, economical and political situations, technical problems, and water demand had a great impact on the removal efficiency of the WTP units.